IFPRI key facts series: Key facts sheet on employment - International Food Policy Research Institute; Jolex, Aubrey (International Food Policy Research Institute, 2022)
This is the third in a series of Key Facts sheets that IFPRI has produced based on the fifth Malawi Integrated Household Survey of 2019/20. The purpose of the series is to present data relevant to key policy issues on agriculture, food systems, and development topics in Malawi.